PERAN PEMBELAJARAN BERKREASI TARI DALAM MENGEMBANGKAN KEMAMPUAN INTERAKSI SOSIAL REMAJA - Fahima Raisya Nakhwin; Dinny Devi Triana; Selly Oktarini (Jurnal Pendidikan Tari, 2025)
Social interaction is a crucial aspect of adolescent development, particularly in building communication, cooperation, and self-confidence. However, many adolescents face challenges in social interaction due to various factors, including social and economic disparities. This study aims to analyze the role of creative dance learning in enhancing adolescents' social interaction skills through the Problem-Based Learning (PBL) model. The research method used is Classroom Action Research (CAR) based on Kurt Lewin’s model, which consists of two learning cycles. The research subjects were 12 students aged 13–15 years at Sekolah Alam Tunas Mulia. Data collection techniques included observation, interviews, questionnaires, and documentation. The research results show that creative dance learning through the PBL model significantly improves students' social interaction. The average social interaction score increased from 33.1 in the pre cycle to 57.9 in the first cycle and reached 80.1 in the second cycle. This improvement occurred because students were engaged in movement exploration, improvisation, and teamwork in groups. Thus, creative dance learning can be an effective strategy for developing adolescents' social interaction, especially for those experiencing social and economic barrierse.